ACCOUNTING SYSTEMS AND PROCEDURES FOR CASH RECEIVING AT SPI HOTEL - Lukieto Cahyadi (Bajang Institute, 2022)
Cash Receipt Accounting System and Procedures at SPI Hotel. The purpose of this study is to find out how the accounting system and procedures for cash receipts at the SPI hotel are. Based on research conducted by Hotel SPI on the cash receipts accounting system, it can be concluded that there are obstacles that can harm the hotel, including: Decreased cash receipts due to the Covid 19 pandemic which makes employees nervous and commits fraud. Controlling functions related to the hotel are somewhat lacking well, even though the schedule of the employees at the reception has been divided based on the shifts, there are still carelessness that causes losses to the hotel. Regarding the documents used in the company, it is based on existing theory, but so that the evidence owned by the company can be used properly for each function, it is necessary to add documents that are more accurate and more effective when using technology. The accounting used in the cash receipts system at the SPI Hotel is not in accordance with the theory that underlies it. The accounting records used are only revenue recapitulation, the company should be able to record in the form of cash receipts journals. The receptionist took inappropriate actions when recording room reservation data that had been registered on a special online application for users. When the receptionist checks the incoming booking, the reservation should be reported directly to a third party. But the reporting procedure is not carried out by the receptionist. So that it becomes a problem that is very influential for the hotel, if it continues to be left without good control it will have a very bad impact.